Individuals with high obsessive-compulsive tendencies or undermined confidence rely more on external proxies to access their internal states. (March 2017) - Zhang, Zhongming; Wang, Mengyun; Miao, Xiaocui; Li, Yijuan; Hitchman, Glenn; Yuan, Zhen
Abstract: Background and Objectives: The Seeking Proxies for Internal States (SPIS) hypothesis predicts that obsessive-compulsive disorder (OCD) is associated with a deficit in subjective convictions, which may lead to a reliance on external substitutes for the perceptions of an individual's internal states. Two well-designed studies were performed for the present work that adopted a false bio-feedback procedure in a muscle tension task to examine the SPIS hypothesis. Methods: The false bio-feedback paradigm was used to investigate our hypothesis. NeXus-10 Mark II hardware and V2011 BioTrace + software (Mind Media B.V., Herten, Netherlands) were utilized to measure the muscle tension of the flexor carpiulnaris muscle, which characterized the target's internal state. In addition, false EMG changes were recorded and displayed on a computer monitor and were considered external proxies. Results: Study 1 demonstrated that the participants with high obsessive-compulsive (OC) tendencies were more affected by the false bio-feedback and exhibited lower confidence in their judgments regarding their muscle tension compared with the participants with low OC tendencies. These findings indicate that subjects with high OC tendencies were more influenced by self-perception effects. In contrast, the subjects in the undermined confidence group in Study 2 were more easily influenced by the false bio-feedback compared with the control group, which suggests that the subjects in the undermined confidence group were more affected by self-perception effects. Limitations: We did not combine the undermined confidence with OC tendencies or OCD symptoms in our paradigm to investigate their joint effects on self-perception. Conclusions: Our findings provide further evidence that supports the SPIS hypothesis, which indicates that OC tendencies and the confidence in an individual's recognition of internal states appear to have similar effects on the assessment of internal states and reliance on proxies. Highlights: Subjective convictions were tested in a false bio-feedback paradigm. Individuals with high obsessive compulsive tendencies were affected more by self-perception effects. Individuals with undermined confidence were affected similarly by self-perception effects.